Preparation of Plaster Moulage (Cast) in Plastic Surgery patients - Roshani E. Rana; Vinita A. Puri; Purnima M. Aiyer; Amresh Baliarsing (Indian Journal of Plastic Surgery)
The purpose of this paper is to describe the technique of making casts using alginate compound for negative and dental stone plaster for positive impressions. With certain modifications a cast could be made of any part of the body and one can make a museum of interesting cases. Casts serve as useful teaching material especially in cleft lip and palate patients to study the effect of surgery on growth and development of the cleft lip-palate-nose complex in relation to the remaining face. It also helps in planning reconstruction in cases of facia! defects, recording serial changes in multistage surgery, pre-operative and post-operative comparison as in rhinoplasty, ear reconstruction, hand etc; for comparing results before and after treatment in keloid and hypertrophic scars, fabrication of implants and preparation of prosthesis. In spite of newer modalities like 3-D imaging and stereolithography, the usefulness of this old technique in certain interesting cases can not be denied.